Ultrasound Guided Musculoskeletal Procedures in Sports Medicine: A Practical Atlas - Sirisena, Dinesh (Elsevier Science & Technology, 2021)
Ultrasound Guided Musculoskeletal Procedures in Sports Medicine: A Practical Atlas provides the support practitioners need based on practical, first-hand experience of a Sports and Exercise Medicine Physician who trained in musculoskeletal sonography.